Evaluation of Safety of a Newly Formulated Pirfenidone in Chronic Kidney Disease: A Non-Randomized Pilot Study in Mexican Patients - Simón A. Ojeda-Duran; Iván Lyra-Gonzalez; Alejandra Meza-Rios; Silvia Lucano-Landeros; Ana Sandoval-Rodriguez; Monica Vazquez-Del Mercado; Arturo Santos; Lucia Flores-Contreras; Juan Armendáriz-Borunda (Journal of Renal and Hepatic Disorders, 2020)
The aim of this pilot clinical trial was to evaluate the safety of a new formulation of prolonged-release Pirfenidone (PR-PFD) in chronic kidney disease (CKD), specifically focal and segmental glomerular hyalinization (FSGH). Open-label, pilot, nonrandomized trial. Eighteen patients previously diagnosed with CKD stages 1– 5 according to “Kidney Disease: Improving Global Outcomes” were enrolled in the study. Target dos-age of PFD was 1200 mg twice a day in the form of prolonged-release tablets to reach a full dosage of 2400 mg daily. Clinical trial was carried out for 60 months to evaluate the safety and efficacy of a newly formulated PR-PFD in patients with CKD. After the treatment for 60 months, it was found that PR-PFD kept renal function from declining significantly in CKD patients, as the glomerular filtration rate (GFR) showed only minimal variations throughout the study. Estimated glomerular filtration rate (eGFR) showed no differences at both baseline and the end points. Proteinuria improved, and creatinine, cystatin C, urea, hemoglobin and hepatic transaminases remained constant without any considerable changes across the study. Minor side effects were noticed when compared with those found in previous studies, indicating an increased tolerance to this pharmaceutical formulation of PFD. Prolonged-released PFD could be safely used as an adjuvant therapy in patients with CKD. Registry number was obtained from ClinicalTrials.gov (NCT02408744).